2019
DOI: 10.1002/celc.201901708
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Evolution Reaction on Single‐Walled Carbon Nanotubes Noncovalently Functionalized with Metal Phthalocyanines

Abstract: This work reports the facile preparation of single-walled carbon nanotubes (SWCNTs) noncovalently functionalized with 3d transition metal (II) phthalocyanines MPcs (M=Mn, Fe, Co and Ni) and their electrochemical evaluation towards the oxygen evolution reaction (OER) in alkaline media. The modification of SWCNTs with MPcs improved the potential required for the oxygen evolution reaction in 0.1 M and 1 M KOH by lowering the potential by approximately 120 mV in comparison with unmodified SWCNTs, at a current dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 72 publications
1
20
0
1
Order By: Relevance
“…Recently, single-walled CNTs noncovalently functionalised with MPcs (FePc; MnPc; NiPc; CoPc) was reported, but even the best performing electrocatalyst (SWCNT + NiPc) in more concentrated electrolyte solution (1 M KOH) exhibited E OER of 1.6 V [70] that is comparable with the result obtained herein by pyrolysis of MPcs and CNTs indicating that pyrolysis generates more OER-active sites. Niu and co-workers prepared porous NiCoP/NSP-HPCNS catalyst that exhibited good electrocatalytic activity for OER with only 299 mV overpotential at 10 mA cm À 2 in 1 M KOH instead of 0.1 M KOH as used here.…”
Section: Nicon-cnt)supporting
confidence: 79%
“…Recently, single-walled CNTs noncovalently functionalised with MPcs (FePc; MnPc; NiPc; CoPc) was reported, but even the best performing electrocatalyst (SWCNT + NiPc) in more concentrated electrolyte solution (1 M KOH) exhibited E OER of 1.6 V [70] that is comparable with the result obtained herein by pyrolysis of MPcs and CNTs indicating that pyrolysis generates more OER-active sites. Niu and co-workers prepared porous NiCoP/NSP-HPCNS catalyst that exhibited good electrocatalytic activity for OER with only 299 mV overpotential at 10 mA cm À 2 in 1 M KOH instead of 0.1 M KOH as used here.…”
Section: Nicon-cnt)supporting
confidence: 79%
“…But even the best E OER result obtained with SWCNT + NiPc (1.6 V, obtained in 1 M KOH)68 is 20 mV more than the E OER of the as-synthesized FeNiN-MWCNT studied in 0.1 M KOH herein. Thus, since FeNiN-MWCNT and FeCoN-MWCNT exhibited good OER activity among the prepared electrocatalysts, it suggests that Fe and Ni or Co metal-N 4 macrocycles together could strongly enhance the OER kinetics.…”
mentioning
confidence: 57%
“…67 Also, very recently, better OER activity on single-walled carbon nanotubes (SWCNTs) noncovalently functionalized with single MPc (e.g., NiPc, MnPc, FePc, CoPc) in terms of achieving 10 mA cm −2 was obtained in 1 M KOH than 0.1 M KOH. 68 It was found that FeNiN-MWCNT retained 82% (Figure 5b) and FeCoN-MWCNT retained 81% (Figure S9b) of the initial OER current densities after 10 000 s. As can be seen, both electrocatalysts, FeCoN-MWCNT and FeNiN-MWCNT, are very electrochemically active and stable for the ORR and OER, respectively.…”
Section: Characterization Of the Catalystsmentioning
confidence: 77%
“…Graphene has two forms of interactions that influence its compatibility with other nanomaterials or stimulants between electron-rich and electron-poor regions [30]. This is often seen on both face-to-face arrangement and edge-to-face arrangement [31]. Also present in biologically relevant molecules such as DNA, RNA, and porphyrins through electron interactions.…”
Section: Methods Of Synthesis Of Carbon Nanocompositesmentioning
confidence: 99%